A retrospective study of the prevalence of herpes simplex virus and herpes zoster virus infection - Radzuan, Maryam; Sufiawati, Irna; Sandiono, Dendi (Universitas Padjadjaran, 2014)
Introduction: Herpes simplex virus (HSV) and herpes zoster virus (HZV) are two members of the herpes virus family that can manifest in oral mucosa. Following primary infection, the viruses remain latent and may reactivate if the immune system becomes compromised. The purpose of this study was to know the prevalence and the site of manifestation of HSV and HZV infection in RSUP Hasan Sadikin Bandung from January 2007 until December 2011. Method: The method of this study was descriptive retrospective using secondary data and literature study. Data were taken from medical records of patients in RSUP Hasan Sadikin Bandung, from January 2007 until December 2011. The results were then presented in table and graphs. Result: The study’s result showed the prevalence of HSV infection from 2007-2011 was 6% while the prevalence of HZV infection was 46%. HSV and HZV infection occurred 41% at head and neck, 36% at trunk, 13% at extremities, 7% generalized, and 3% unspecified. The systemic diseases involved in these herpes viruses found in 20.3% patients. Conclusion: The conclusion of this study were the prevalence of HSV infection was low, while the prevalence of HZV infection was high. HSV infection frequently affected at head and neck, and HZV infection frequently affected the trunk. Systemic diseases involved in these herpes viruses were malignancies, neoplasm, internal organ disorders, skin diseases, blood disorder, and nerve disorder.